The artistic truth: coherence, cohesion and credibility in Jane Austen’s novels - Ángel Jordán, Miguel (International Journal of English Literature and Social Sciences (IJELS), 2019)
Any literary work is composed of different elements both in its formal part and in the subject matter. The author's mission is to achieve that these elements fit harmoniously, so that the work is perceived as a whole and not as a merger of parts. To achieve this unity in the work, it is essential that there is internal cohesion between its different elements. And coherence in the argument and its various parts will also be necessary for the reader to perceive it as something logical and, in this way, to create the sensation of reality that a work of fiction must provide. In this article, we will analyze some of the strategies used by Jane Austen to give unity to her work and confer on her stories the degree of credibility needed.